A2.16 Inhibition of lymphocyte activation in primary Sjögren syndrome (PSS). (13th February 2015) - Legány, N; Toldi, G; Megyes, N; Orbán, C; Kovács, L; Balog, A
Abstract : Objectives: Primary Sjögren's syndrome (pSS) is an autoimmune diseases characterised by ocular and oral dryness due to the progressive destruction of lachrymal and salivary glands by an inflammatory process. The short-term activation of peripheral blood and exocrin glands T lymphocytes plays a crucial role in initiating and maintaining the chronic inflammation. The transient increase of the cytoplasmic free calcium level plays a key role in the process of lymphocyte activation. Kv1.3 and IKCa1 potassium channels are important regulators of the maintenance of calcium influx during lymphocyte activation. The influx of calcium is maintained by the function of potassium channels that conserve the electrochemical potential gradient via the efflux of potassium from the cytoplasm. Recent reports raised the notion that the inhibition of lymphocyte potassium channels, especially that of the Kv1.3 channel would be an optimal solution for specific immunosuppression in autoimmune disorders. Therefore, in this study we aimed to characterise the effects of lymphocyte potassium channel inhibition on short-term peripheral blood T lymphocyte activation in major lymphocyte subsets in pSS. Methods: We enrolled 8 healthy individuals and 15 pSS patients. We evaluated calcium influx kinetics following activation in CD4, Th1, Th2 and CD8 cells applying a novel flow cytometry approach. We assessed the sensitivity of the above subsets to specific inhibition of the Kv1.3 and IKCa1 potassium channels. We also assessed the Kv1.3 expression on lymphocytes. Results: The peak of calcium influx in lymphocytes isolated from pSS patients is reached later, indicating that they respond more slowly to stimulation compared to controls. In healthy individuals, the inhibition of the IKCa1 channel decreased calcium influx in Th2 and CD4 cells to a lower extent than in Th1 and CD8 cells. On the contrary, the inhibition of Kv1.3 channels resulted in a larger decrease of calcium entry in Th2 and CD4 than in Th1 and CD8 cells. Neither the inhibition of IKCa1 channel nor the inhibition of Kv1.3 channels has an influence on intracellular calcium kinetic in pSS. The expression of Kv1.3 channels on CD4, Th2 and CD8 lymphocytes was significantly higher compared to controls. Conclusion: There is an alteration of the short-term activation of peripheral lymphocytes in pSS. The inhibition of Kv1.3 and IKCa1 channels does not seem to be specific enough in peripheral pSS lymphocytes. The overexpression of Kv1.3 channels in pSS might be a compensatory mechanism of the dysfunction of Kv1.3 and IKCa1 channels, theoretically.